Genetic associations with lymphomas in Polish patients: A pooled‐DNA genome‐wide association analysis. (29th August 2022) - Paszkiewicz‐Kozik, Ewa; Kluska, Anna; Piątkowska, Magdalena; Bałabas, Aneta; Żeber‐Lubecka, Natalia; Karczmarski, Jakub; Goryca, Krzysztof; Kulecka, Maria; Wojciechowska‐Lampka, Elżbieta; Osiadacz, Włodzimierz; Romejko‐Jarosińska, Joanna; Świerkowska, Monika; et al.
Abstract: Several single nucleotide polymorphisms (SNPs) associated with susceptibility to Hodgkin lymphoma (HL) and diffuse large B‐cell lymphoma (DLBCL) have been identified. The aim of this study was to identify susceptibility loci for HL and DLBCL in Polish patients. Altogether, DLBCL ( n = 218 and HL patients ( n = 224) and healthy individuals ( n = 1181) were recruited. Lymphoma diagnosis was based on standard criteria. Genome‐wide association study (GWAS) was performed using pooled‐DNA samples on llumina Infinium Omni2.5 Exome‐8 v1.3, and selected loci were replicated by TaqMan SNP genotyping of individuals. GWAS detected thirteen and seven SNPs associated with DLBCL and HL, respectively. In the replication study, six and seven SNPs reached significance after correction for multiple testing in the DLBCL and HL cohorts, respectively. One and four SNPs associated with DLBCL and HL, respectively, were localized within, and two SNPs—near the major histocompatibility complex (MHC) region. In conclusion, the majority of loci associated with HL and DLBCL aetiology in previous studies have potential roles in immune function. Our pooled‐DNA GWAS enabled the identification of several susceptibility loci for DLBCL and HL in the Polish population; some of them were mapped within or adjacent to the MHC, and other associated SNPs were located outside the MHC.